Sanitary quality of the public groundwater supply for the municipality of Belém in northern Brazil - Rodrigo Santos de Oliveira; Daniela Mayumi Kiyatake; Maria Lúcia Harada; Karla Tereza Silva Ribeiro (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2013)
The present study verified the quality of the water of Água Preta Lake, which is part of the public supply for the Northern Brazilian municipality of Belém (Pará State). Six samples were collected from each of six sampling points. The concentration (NMP) of coliforms was determined by Multiple-tube fermentation Technique. The isolates of Escherichia coli obtained from the samples were tested for susceptibility to the antibiotics (cefoxitin, ampicillin, imipenem, gentamicin, and amikacin). Furthermore, was analyzed the presence of diagnostic genes for the diarrheagenic strains of E. coli. None of the genes was identified, however, the recorded concentrations of thermo-tolerant coliforms were within the recommended limits for standing water sources used for public supplies. Nevertheless, the highest concentrations of total and thermo-tolerant coliforms were recorded at two points, one adjacent to the most densely-populated area of the lake margin, and the other near the catchment area for water from the Guamá River. The susceptibility testing indicated the presence of six resistance phenotype profiles, including multi-resistant strains. The results of the study reinforce the need for the systematic monitoring of this water source, in order to provide guidelines for the development of effective management policies for public water supplies, as well as the prevention of water-borne diseases.